Effect of fiber reinforced polymer on mechanical performance of 3D printed cementitious material - Lim, Jian Hui (2018)
Cementitious material is mechanically brittle and weak in tensile by nature. Moreover, 3D printed cementitious material is orthotropic and have a weakness line between layers. Conventional reinforcement technique for concrete utilizes rigid rebars to impart mechanical performance of concrete structures and improve its loading carrying capacity. However, rigid rebars limit the free-form capabilities of additive manufacturing and goes against its freedom of design principle. To overcome this issue, glass fiber reinforced polymer and carbon fiber reinforced polymer sheets were used to reinforced 3D printed cementitious material in this study. The reinforced printed concrete specimens were tested on four-point bending test, and the influence of FRP on 3D printable mortar and fiber reinforced mortar were analyzed based on load capacity, ductility, fracture energy and failure mode.